2022
DOI: 10.4178/epih.e2022029
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in opioid prescriptions in Korea from 2002 to 2015 based on the Korean NHIS-NSC cohort

Abstract: Cohort between 2002 and 2015. Methods: Morphine milligram equivalent (MME) was calculated to standardize the relative potency of the opioids. The number (cases) or amount (MME) of annual opioid prescription per 10,000 registrants was computed to analyze trends of consumption of opioids after age standardization. Joinpoint regression analysis was conducted to calculate the annual percentage change and average annual percentage change (AAPC). Results: The number (cases) of prescriptions per 10,000 registrants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(46 reference statements)
0
5
1
Order By: Relevance
“…Temporary fluctuations were observed when analyzing the trend in opioid analgesic prescriptions over the past four years; however, no significant overall change was noted. This trend is in contrast with a previous report that showed a sharp increase in opioid prescriptions in South Korea from 2002 to 2015 [ 13 ]. A previous study found that an opioid abuse prevention program within the NIMS reduced opioid overdose events [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Temporary fluctuations were observed when analyzing the trend in opioid analgesic prescriptions over the past four years; however, no significant overall change was noted. This trend is in contrast with a previous report that showed a sharp increase in opioid prescriptions in South Korea from 2002 to 2015 [ 13 ]. A previous study found that an opioid abuse prevention program within the NIMS reduced opioid overdose events [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“… 17 In the United States, death due to opioid-related overdoses have tripled, increasing from 2006 to 2016, and health care costs, criminal justice expenses, and productivity losses associated with opioid misuse were estimated to total $78.5 billion. 18 19 Moreover, cohort studies in Korea have reported that the number of opioid users in the general population has increased and that opioid use is associated with increased mortality, 11 12 20 suggesting that long-term opioid use is becoming a major public health concern that cannot be ignored in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The MME was also increased 15.06 to 40,727.8 during the same period. Fentanyl had increased most rapidly among prescription opioids (morphine, oxycodone, fentanyl, and hydromorphone) [ 110 ]. Chronic weak opioid users increased from 1.03% in 2002 to 9.62% in 2015, and strong opioid users increased from 0.04% in 2002 to 0.24% in 2015 [ 111 ].…”
Section: Main Bodymentioning
confidence: 99%